Prospecção de genes relacionados à ocorrência de enfermidades no camarão Litopenaeus Vannamei (Boone, 1931) sob condições de cultivo - Feijó, Rubens Galdino (2009)
The marine shrimp culture has achieved great importance in the global economy as an agriculture business, not only for jobs and income generation, but especially because it represents a viable alternative source of animal protein for the growing global food demand. However, the occurrence of diseases in shrimp culture, especially those of viral aetiology, has significantly compromised the activity, causing high mortality rates and consequent economic loss. The identification and characterization of genes related to shrimp diseases has helped understanding the immune responses triggered in the infectious processes, and mechanisms related to host-pathogen interaction, about which very little is known at the moment. The main objective of the present work was the prospection and characterization of genes related to diseases of the shrimp species Litopenaeus vannamei under typical rearing conditions. The health status investigation of 40 shrimps by histopathological and molecular methods of diagnosis resulted in the detection of IMN, IHHN, WSS, NHP, vibriosis and gregarines in various degrees and combinations. Shrimps have been grouped in classes for gene prospecting through the technique of Differential Display RT-CR (DDRT-PCR). The analysis of differential gene expression in the profiles produced resulted in the identification of three previously undescribed gene sequences potentially related to the occurrence of diseases in shrimp L. Vannamei. Two of these sequences (882-A1R2 and 730-A4R10) have not had homologies to any annotated invertebrate sequences. Fragment 842-A2R6 however, showed 99% nucleotide similarity with the mut-7 gene, which encodes a type of RNAse involved in the mechanism of post-transcriptional gene silencing through RNAi in the nematode Caenorhabditis elegans. It is suggested hare that this kind of mechanism may be involved in the silencing of double stranded RNA from viruses like the IMNV.